Beijing [videorecording (DVD)] (Pilot guides., 2004)
Beijing is China's capital located in the Northeast of this vast country. The stops featured on the way include: The Forbidden City, Silk Street Market, Tiananmen Square, Chang'an Avenue, The Great Wall, Kung Fu, Chinese Opera, and Temple of Heaven.